PHYTOACCUMULATION OF CHROMIUM(VI) METAL ION BY SNAKE PLANT (Sansevieria tifasciata Prain) - Nini Astuti Alwi; Asmawati Asmawati; Syarifuddin Liong (Jurnal Akta Kimia Indonesia (Indonesia Chimica Acta), 2018)
Snake plant (Sansevieria trifasciata Prain) used as one of the phytoremediation techniques to absorb chromium metal. Snake plants (Sansevieria trifasciata Prain) to accumulate ion of Cr(VI) from the soil by using variation of pollutant concentration and time variation. Pollutant concentration used were 100; 200; 400; and 800ppm. The concentration of metal ions Cr(VI) that has been absorbed can be determined using Atomic Absorption Spectrophotometer (AAS). The result showed that the accumulation of metal ions Cr(VI) on snake plant biggest in the third week which is 6,30 mg/kg dry weight. Types or phytoremediation mechanisms that occur in the accumulation of Cr(VI) in snake plant is rhyzofiltration. Based on the result of snake plant are not potentially as hyperaccumulator plant of Chrom.